Investigating high schoolers’ L2 writing anxiety, L2 writing self-efficacy, L2 writing self-regulated strategies, and L2 writing engagement: Relationships and mediator - Zhou, Jie; Wang, Shusheng; Wang, Junju (Frontiers in Psychology, 2022)
This study used a structural equation modeling approach to investigate the relationships among L2 writing anxiety, L2 writing self-efficacy, L2 writing self-regulated strategies and L2 writing engagement, and possible mediators that regulate the effect of individual factors. A questionnaire was administered to 340 Chinese high school students from different parts of the country. The results of the study suggested a negative relationship between L2 writing anxiety and L2 writing self-efficacy, and a direct effect of both on L2 writing engagement. While a higher level of L2 writing self-efficacy indicated a lower level of L2 writing anxiety and more students’ L2 writing engagement, L2 writing efficacy had a much stronger direct effect on L2 writing engagement than L2 writing anxiety. In addition, L2 writing self-regulated strategies were found to play a mediating role between L2 writing self-efficacy and L2 writing engagement, but not between L2 writing anxiety and L2 writing engagement. This study helps to understand the interplay of individual factors related to L2 writing and sheds light on promoting English writing abilities of Chinese high school students.